Procréations médicalement assistées, sexualité et religions - Corinne Fortier (Ateliers d'Anthropologie)
The rapid development of procreation techniques has had the consequence of detaching gametes (the sperm and egg) from the rest of the person’s body, by making it possible to extract them for laboratory reproduction in vitro—no longer in vivo during a sexual relationship. But these forms of reproduction without any sexual relationship nevertheless have a sexual character. In fact, even though it is taken for granted that assisted reproductive technologies have separated procreation from sexuality, the latter is far from having vanished from this way of procreating, as forcefully revealed by an examination of monotheistic religions with regard to these new techniques, especially when the techniques involve a third party, reviving the spectre of adultery and incest. On these subjects, Islam will be compared with other monotheisms, specifically Judaism and Roman Catholicism.